PEMIJAHAN IKAN BETOK (Anabas testudineus Bloch) YANG DIINDUKSI DENGAN EKSTRAK HIPOFISA AYAM BROILER - Nicky Fara Diba; muslim .; yulisman . (Universitas Sriwijaya, 2016)
ABSTRACT The climbing perch (Anabas testudineus) is very difficult to spawn naturally in the cultivation environment. The aim of this research was to know the best dose of broiler pituitary extract for latency period, fecundity, fertilized egg percentage, hatching egg percentage, survival rate of climbing perch (D1-D3) larvae. This research had been conducted from April-May 2015 at Laboratory of Budidaya Perairan,Â Aquaculture Department, Faculty of Agriculture, Sriwijaya Unversity, Indralaya. This research method used completely randomized design (CRD) with four treatments and three replications. Females broodstock were induced by broiler pituitary extract with different doses that were, 400 mg/kg, 500 mg/kg, 600 mg/kg body weight and Induced by that synthetic gonadotrophin hormone (positif control) 0,5 ml/kg body weight. The parameters observed during the research were latency period, fecundity, fertilized egg percentage, hatching egg percentage, survival rate of climbing perch (D1-D3) larvae and water qualities. The result of this research showed that if considered from latency period and fecundity that synthetic gonadotrophin hormone more effective compared with broiler pituitary extract, but if in terms of the fertilized egg percentage, hatching egg percentage, and survival rate of climbing perch (D1-D3) larvae, that synthetic gonadotrophin hormone as effective as broiler pitutary extract. The range of water qualities were temperature 28-30 0C, pH 5.34-6.98, DO 3.13-5.97 ppm, and ammonia 0.009- 0.0018 ppm. Key words : Climbing perch, spawning, broiler pituitary extract